Understanding of the fruit farmers’ adoption intention toward organic farming - Wan Abdullah, Wan Nor Syafikah; Mohamad Shukri, Nur Anisah Syafiqah; Md Zain, Norhafizah; Abdullah, Farah Adilla; Zakaria, Suhana; Abu Bakar, Tengku Halimatun Sa’adiah T; Man, Norsida; Arif Shah, Jasmin (RSIS International, 2024)
Organic farming practices have been encouraged in Malaysia’s agricultural industry to promote sustainable and environmentally friendly growth. Besides, it is also in line with Sustainable Development Goals (SDG) which are goals number three (SDG 3) and thirteen (SDG 13). Johor is a state located in the southern region of Peninsular Malaysia with varieties of fruits planted such as pineapple, durian, and other local fruits. Hence, based on the data from the Department of Agriculture (DOA), Johor recorded the highest number of fruit farmers with 36,655. However, only 5 of the fruit farmers in Johor received the Malaysian Organic Certification Scheme (myOrganic). Thus, the purpose of this research is to develop a framework for intention on organic farming practices to ensure food safety and security among fruit farmers in Malaysia. The Theory of Planned Behaviour (TPB) and the Technology Acceptance Model (TAM) were employed in this study. Through quantitative research design, the questionnaire was distributed to the 119 fruit farmers in Johor by using simple random sampling. In this study, SPSS version 26.0 was used and data was examined by using a descriptive test, and Spearman’s test. The findings of this study concluded that the mean score on adoption intention among fruit farmers in Johor was M= 2.5966 which is categorized as a moderate mean value. Meanwhile, the results for the relationship between all the factors significantly influence on organic farming adoption intention. This study can contribute to the literature and provide a better understanding of the factors that influence the intention on organic farming including factors of attitude and perceived ease of use.